A influência das atividades de educação empreendedoras sobre as características e atitude empreendedora dos alunos de graduação da Universidade Federal de Santa Maria UFSM - Balconi, Silvana Bortoluzzi (2016)
This study aimed to analyzed the influence of entrepreneurial education activities on the entrepreneurial characteristics of undergraduate students at the Federal University of Santa Maria, Campus PM. Was conducted a qualitative and quantitative exploratory case study, based on empirical research. Informal data collection was gathered with the objective to identify which teachers, in the opinion of the students, perform different activities in the classroom. For the qualitative research, a semi-structured interview was performed with five teachers. For data analysis, was adopted the method of content analysis. From this analysis emerged methods of teaching activities, teacher-student interaction and entrepreneurial learning. For the quantitative research was applied a questionnaire developed by David McClelland (1971) which was answered by 792 undergraduate students. The internal consistency of the scales was evaluated by Cronbach s alpha coefficient, taking into account the reliability for the measurement and evaluation of the constructs. Data were analyzed using statistical tests. Regarding the results of the questionnaires, it can be stated that the intensity of entrepreneurial characteristics less present in students are taking calculated risks, persuasion and contact networks. The association of the two approaches was performed by the triangulation technique. As a result, it was found that, from the less present entrepreneurial characteristics in students, it requires reflection, in order to provide adherent practical activities to the peculiarities and the concept of these characteristics, for the moment that enhances practices aimed to develop entrepreneurial characteristics in the classroom, it is providing the student with a different way of learning. The statement that students recognize the teacher who practices different approaches in the classroom, shows that the practices that increase entrepreneurial characteristics and attitudes of students are a fact and a necessity for the learning process.